Analysis of the School Committee's Understanding of Duties and Functions at Public Elementary Schools in Pantai Labu District - Sigit Maulana Ismanda; Arif Rahman; Zulkifli Matondang (Yayasan Pendidikan Bima Berilmu, 2026)
This study was motivated by the suboptimal role of school committees in elementary education governance, particularly in understanding their duties and functions as advisory, supporting, controlling, and mediating bodies. The urgency of this research lies in the importance of school committee understanding as a foundation for community participation in improving education quality. This study aimed to describe school committees' understanding of their duties and functions in public elementary schools in Pantai Labu District. This research used a qualitative approach with a descriptive method. The informants consisted of principals, school committee chairpersons, committee members, and teachers selected through purposive sampling. Data were collected through interviews, observation, and documentation studies, then analyzed through data reduction, data display, and conclusion drawing. The results show that school committees understand their position as school partners, but they do not yet have a comprehensive understanding of their advisory, supporting, controlling, and mediating functions. Their role remains largely administrative, such as attending meetings, approving programs, and signing school documents. This study concludes that school committee understanding needs to be strengthened through socialization, training, mentoring, work program development, and regular communication forums so that committees can contribute more effectively to improving elementary education quality.